EVIDENCE-BASED GINGER COMPRESS THERAPY FOR REDUCING LOW BACK PAIN IN THIRD-TRIMESTER PREGNANT WOMEN - Sopiatun, Siti; Yani, Yanah Fitri (Mitra Husada Health Internasional Conference (MIHHICo), 2026)
Introduction: Back pain is a common problem experienced during pregnancy. Various factors contribute to this condition, including uterine growth, weight gain, the effect of the relaxin hormone on ligaments, a history of back pain, parity, and daily activities. If not managed properly, back pain may persist after childbirth and become chronic. Objective: This implementation aimed to evaluate the effectiveness of ginger compresses in reducing back pain among pregnant women. Methods: The study used a case report approach involving two third-trimester pregnant women. The intervention was conducted over four visits, with ginger compresses applied three times, each session lasting 15 minutes. Pain intensity was assessed using the Numeric Rating Scale (NRS). Pain scores were measured before and after the application of the ginger compress. Results: showed a reduction in pain intensity in both participants. The first pregnant woman had an initial pain score of 5 (moderate pain), while the second pregnant woman had an initial pain score of 6 (moderate pain). At the end of the intervention, both participants experienced a decrease in pain. Conclusions: The implementation of ginger compress to reduce back pain was effective in reducing back pain intensity among third-trimester pregnant women.